Stability of a two wheels mobile robot using robust control - Halim Zakaria, Othman (2009)
The research on two wheels mobile robots or commonly known as balancing robots have gained momentum over the last decade in a number of robotic laboratories around the world, The objectives of this thesis are to present a modeling of a two wheels mobile robot and the design of Sliding Mode Control (SMC) for the system. A robust controller based on Sliding Mode Control is proposed to perform the robust stabilization and disturbance rejection of the system. In order to compensate the disturbances, position, speed, angle and angle rate of the two wheels mobile robot will be observed. The performance of the proposed controller will be compared to the pole placement techniques. A computer simulation study is carried out to access the performance of the proposed control law.